Global Economic Stratification and the Evolving Role of China in the Developing World - Grell-Brisk, Marilyn (Neuchâtel : Université de Neuchâtel, 2018)
This thesis examines global inequality through the lens of global economic stratification and explores how China’s upward mobility has impacted both other developing countries, and the structure of the worldeconomic hierarchy. Through case studies, I analyze the ways in which certain countries adapt to the changing structure of the world-economy and how their responses reflect the global and structural transformations occurring at the world-system level. The approach is mixed quantitative/qualitative and macro-comparative, with an emphasis on interactions within the modern capitalist world-system. Findings are as follows: a) China’s movement into the middle stratum of the stratified world-economy has caused a shift away from the classic Wallersteinian trimodal economic distribution; and b) that this shift has created an unprecedented over-crowding effect in the semiperiphery. This is generating new systemic pressures that engender the spread of regional and multilateral organizations such as the Asia Infrastructure Investment Bank, the ASEAN Free Trade Area and Bolivarian Alliance for the Americas. On the other hand, this systemic pressure can foster a more aggressive and confrontational core-semiperiphery-periphery relationship. c) that with these new regional and multilateral organizations, changing notions of national identity and citizenship especially within the transnational capitalist class (particularly with those of Chinese origins) have the potential to affect not only geopolitics but also to further impact the categorical between-country inequality and global stratification. d) that Sub-Saharan Africa as a region remained at the bottom of the stratified world-economy; e) but there were notable advances at the country level; f) that the upward movement of individual SSA countries within the hierarchy were in part, largely due to external factors such as engagement with China and political support from the Occident; g) and availability and exploitation of natural resources worked considerably to the benefit of SSA countries. This thesis attempts to change the direction of the discourse on the rise of China away from questions of hegemonic ascent, to the impact of China’s advancement within the structural confines of the modern capitalist world-economy. Current research on global economic stratification have not focused on Sub-Saharan Africa so this is an attempt to rectify this gap in the literature. It also contributes to the growing discourse of China’s engagement with the African continent and the Global South.
La Stratification Économique Globale et le Rôle Évoluant de la Chine dans les Pays en Développement
Keywords: rise of China; China and the Global South; China-Africa relations; Commodified Citizenship; transnational capitalist class